Positive Politeness Strategy in the Conversation of "Me Before You" Movie - Febriyani, Ni Putu Wahyu; Sutjiati Beratha, Ni Luh; Sukarini, Ni Wayan (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 2 (2023): Volume 2 No 2, April 2023, 2023)
This paper entitled “Positive Politeness Strategy in the Conversation of Me Before You Movie”. The aims was to identify the positive politeness strategy and to explain the factor influencing the characters used positive politeness strategies based on the theory of Brown and Levinson (1987). The data was taken from the utterance between characters in the movie. The data was collected through the documentation method by taking-note technique, this article used qualitative method to analyze the data, the method of presenting data analysis was the informal method. This article used the politeness theory proposed by Brown and Levinson. Based on the theory above, there was nine strategies of positive politeness found in this movie. Furthermore, the factor influencing this article is positive politeness payoff. The results of this article show that in “Me Before You” movie the characters used nine out of fifteen strategies in positive politeness. The nine strategies that was found in the utterances of the characters are strategy 2 (exaggerate), strategy 3 (intensify interest to H), strategy 4 (use in-group identity markers), strategy 5 (seek agreement), strategy 6 (avoid disagreement), strategy 10 (offer and promise), strategy 11 (be optimistic), strategy 12 (include both S and H in the activity), and strategy 15 (give gifts to H (goods, sympathy, understanding, cooperation)). Meanwhile, the factor influencing this article is positive politeness payoffs.